Fabrication and testing of PMOS current mirror-integrated MEMS pressure transducer. Issue 2 (20th December 2019) - Kumar, Shashi; Ropmay, Gaddiella Diengdoh; Rathore, Pradeep Kumar; Rangababu, Peesapati; Akhtar, Jamil
Abstract : Purpose: This paper aims to describe the fabrication, packaging and testing of a resistive loaded p -channel metal-oxide-semiconductor field-effect transistor-based (MOSFET-based) current mirror-integrated pressure transducer. Design/methodology/approach: Using the concept of piezoresistive effect in a MOSFET, three identical p -channel MOSFETs connected in current mirror configuration have been designed and fabricated using the standard polysilicon gate process and microelectromechanical system (MEMS) techniques for pressure sensing application. The channel length and width of the p -channel MOSFETs are 100 µm and 500 µm, respectively. The MOSFET M1 of the current mirror is the reference transistor that acts as the constant current source. MOSFETs M2 and M3 are the pressure-sensing transistors embedded on the diaphragm near the mid of fixed edge and at the center of the square diaphragm, respectively, to experience both the tensile and compressive stress developed due to externally applied input pressure. A flexible square diaphragm having a length of approximately 1, 000 µm and thickness of 50 µm has been realized using deep-reactive ion etching of silicon on the backside of the wafer. Then, the fabricated sensor chip has been diced and mounted on a TO8 header for the testing with pressure. Findings: The experimental result of the pressure sensor chip shows a sensitivity of approximately 0.2162 mV/psi (31.35 mV/MPa) for an input pressure of 0-100 psi. The output response shows a good linearity and very low-pressure hysteresis. In addition, the pressure-sensing structure has been simulated using the parameters of the fabricated pressure sensor and from the simulation result a pressure sensitivity of approximately 0.2283 mV/psi (33.11 mV/MPa) has been observed for input pressure ranging from 0 to 100 psi with a step size of 10 psi. The simulated and experimentally tested pressure sensitivities of the pressure sensor are in close agreement with each other. Originality/value: This current mirror readout circuit-based MEMS pressure sensor is new and fully compatible to standard CMOS processes and has a promising application in the development CMOS-MEMS-integrated smart sensors.